TRANSFORMASI WILAYAH PERBATASAN INDONESIA–MALAYSIA MELALUI STRATEGI BRANDING DESTINASI EKONOMI DAN PARIWISATA - Achmad Chomsun Roziqin; Ahmad Munir (BORJUIS: JURNAL OF ECONOMY, 2026)
This study aims to examine the transformation of the Indonesia–Malaysia border region through destination branding strategies based on economic and cross-border tourism potential. Border areas are no longer viewed merely as administrative and security zones, but also as strategic spaces for trade, tourism, cultural interaction, and regional economic growth. This study uses a library research method with a qualitative descriptive approach by analyzing scientific literature, policy documents, and previous studies related to place branding, destination branding, cross-border tourism, borderland development, and regional economic transformation. The findings show that the Indonesia–Malaysia border region has strong potential to be developed as a competitive economic and tourism destination through the utilization of Border Crossing Posts, local superior products, cultural heritage, natural attractions, and cross-border community mobility. However, this potential has not been fully integrated into a coherent destination branding strategy. Therefore, branding must be understood not merely as a promotional tool, but as a regional transformation instrument that connects local identity, economic activities, tourism experiences, digital promotion, and collaborative governance. The study concludes that an integrated branding strategy can strengthen the image of border areas as productive, safe, inclusive, and attractive destinations for tourists, investors, and business actors. This research contributes conceptually to the development of border destination branding studies and practically to policy formulation for sustainable economic and tourism development in the Indonesia–Malaysia border region.